Role of moesin in HMGB1-stimulated severe inflammatory responses - Lee, Wonhwa; Kwon, Oh Kwang; Han, Min-Su; Lee, You-Mie; Kim, Shin-Woo; Kim, Kyung-Min; Lee, Taeho; Lee, Sangkyu; Bae, Jong-Sup (Thrombosis and Haemostasis, 2015)
Sepsis is a life-threatening condition that arises when the body’s response to infection causes systemic inflammation. High-mobility group box 1 (HMGB1), as a late mediator of sepsis, enhances hyper-permeability, and it is therefore a therapeutic target. Despite extensive research into the underlying mechanisms of sepsis, the target molecules controlling vascular leakage remain largely unknown. Moesin is a cytoskeletal protein involved in cytoskeletal changes and para-cellular gap formation. The objectives of this study were to determine the roles of moesin in HMGB1-mediated vascular hyperpermeability and inflammatory responses and to investigate the mechanisms of action underlying these responses. Using siRNA knockdown of moesin expression in primary human umbilical vein endothelial cells (HUVECs), moesin was found to be required in HMGB1-induced F-actin rearrangement, hyperpermeability, and inflammatory responses. The mechanisms involved in moesin phosphorylation were analysed by blocking the binding of the HMGB1 receptor (RAGE) and inhibiting the Rho and MAPK pathways. HMGB1-treated HUVECs exhibited an increase in Thr558 phosphorylation of moesin. Circulating levels of moesin were measured in patients admitted to the intensive care unit with sepsis, severe sepsis, and septic shock; these patients showed significantly higher levels of moesin than healthy controls, which was strongly correlated with disease severity. High blood moesin levels were also observed in cecal ligation and puncture (CLP)-induced sepsis in mice. Administration of blocking moesin antibodies attenuated CLP-induced septic death. Collectively, our findings demonstrate that the HMGB1-RAGE-moesin axis can elicit severe inflammatory responses, suggesting it to be a potential target for the development of diagnostics and therapeutics for sepsis.
Keywords: Moesin; HMGB1; vascular permeability; sepsis; marker